1997
DOI: 10.1055/s-2008-1071079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Suturing Technique and Material on Complication Rate Following Hypospadias Repair

Abstract: Ninety-seven children with distal hypospadias were treated surgically using perimeatal-based flap urethroplasty (Mathieu procedure) in a two and a half years period. A review of the medical records revealed two distinct groups of patients according to the suturing type and suture material. In the first group of 36 patients (group I), neourethra was constructed using 6/0 polyglactine (Vicryl) in a single layer, full-thickness, uninterrupted fashion. Skin flaps were approximated using interrupted simple 5/0 poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 0 publications
3
45
0
2
Order By: Relevance
“…These results implicate that although both suture materials are adequate and appropriate for hypospadias repair in children, polydioxanone had a better cosmetic and long-term outcome because of its rapid absorption time, leading to rapid disappearance of the skin sutures and less skin tracts. As opposed to the results of DiSandro and Palmer [19] in this respect, Ulman et al [7] also found that urethroplasty using polydioxanone suture material is associated with lower complication rate such as fistula formation. Cimador et al [20] questioned the role of suture materials in the complication rate after flap urethroplasty procedures.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These results implicate that although both suture materials are adequate and appropriate for hypospadias repair in children, polydioxanone had a better cosmetic and long-term outcome because of its rapid absorption time, leading to rapid disappearance of the skin sutures and less skin tracts. As opposed to the results of DiSandro and Palmer [19] in this respect, Ulman et al [7] also found that urethroplasty using polydioxanone suture material is associated with lower complication rate such as fistula formation. Cimador et al [20] questioned the role of suture materials in the complication rate after flap urethroplasty procedures.…”
Section: Discussionmentioning
confidence: 84%
“…In hypospadias surgery the most important issue is preservation of the function and esthetic outcomes [4]. The outcome of hypospadias repair surgery depends on the technique and the instrumentation including suture material used and the suturing technique employed [4,5,6,7]. Choosing appropriate suture material for hypospadias surgery depends on several factors including personal preferences, availability and types of material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of suturing policy is reported for the first time in Hypospadias surgery literature. These sutures are water tight and if sutures breaks in between the whole suture line does not unwind [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fistül gelişiminde kullanılan sütür materyalinin önemi yapılan bazı çalışmalarla gösterilmiştir (11). 6-0 polyglicolic asit ile tam kat devamlı sütürle yapılan onarımla, 7-0 PDS ile subepitelyal devamlı sütürle yapılan onarımın karşılaştırıldığı bir çalışmada; PDS kullanılarak yapılan subepitelyal devamlı sütür onarımında fistül oranı daha düşük bulunmuştur (12). Plate derinliğinin önemli olduğunu gösteren çalışmaların yanında, bir önemi olmadığını vurgulayan çalışmalar da mevcuttur (13,14,15 …”
Section: Discussionunclassified